EXCESS MOLAR VOLUMES AND DEVIATIONS IN VISCOSITY OF THE BINARY MIXTURES OF 1-PENTANOL + AROMATIC HYDROCARBONS AT T = 298.15 K - Shamima Aktar; M. Abdur Rahaman; M. Kamrul Hossain; M. Shahadat Hossain; Shamim Akhtar (European Scientific Journal, ESJ, 2015)
The densities, ρ and viscosities, η of pure 1-Pentanol, toluene, ethylbenzene, propylbenzene, and those of their binary mixtures covering the whole composition range have been measured at 298.15 K under atmospheric pressure. Excess molar volumes, E Vm , partial molar volumes, Vi , deviations in viscosity, ∆η and excess free energies of activation, E G# ∆, have also been calculated from the ρ and η data. To obtain correlation coefficients and standard deviations E Vm , ∆η and E G# ∆were fitted to Redlich–Kister type function in terms of mole fraction. In the whole range of composition, E Vm were found to be positive for 1-pentanol + ethylbenzene and + propylbenzene, but 1-pentanol + toluene system showed negative E Vm in the alcohol-rich region for. The ∆η and E G# ∆ values were the negative for all the binary mixtures.